2019
DOI: 10.2174/1874149501913010082
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Modified High Permeable Concrete with a Crumb Rubber

Abstract: Background: High permeable concrete is designed with high porosity, which allows water to pass through it. By considering this ability, it has been widely used for various applications including high permeable road pavement. However, to fully adopt highly permeable road pavement technology is challenging due to high cost and maintenance, besides the present engineers and contractors have insufficient expertise and experience with this technology. Henceforth, the high porosity property is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Therefore, graphene motivated vast investigation interests due to its impressive characteristics, aiming at the discovery of new innovative nanomaterials in this construction era, with its application in ECC intriguing numerous scientists worldwide [ 39 , 40 ]. It is reported that the incorporation of rubberized ECC with GO revealed that the use of coarse crumb rubber is lower than the use of fine crumb rubber [ 41 ]. This indicates that the upsurge in the volume of crumb rubber marginally reduces the strength and penetrability in the concrete mass; thus, this developed mixture of rubberized ECC integrated with GO can be potentially used in the fabrication of several construction materials for applications such as road pavement/basement and filling voids, while it also enhances the freeze–thaw resistance and ductility [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, graphene motivated vast investigation interests due to its impressive characteristics, aiming at the discovery of new innovative nanomaterials in this construction era, with its application in ECC intriguing numerous scientists worldwide [ 39 , 40 ]. It is reported that the incorporation of rubberized ECC with GO revealed that the use of coarse crumb rubber is lower than the use of fine crumb rubber [ 41 ]. This indicates that the upsurge in the volume of crumb rubber marginally reduces the strength and penetrability in the concrete mass; thus, this developed mixture of rubberized ECC integrated with GO can be potentially used in the fabrication of several construction materials for applications such as road pavement/basement and filling voids, while it also enhances the freeze–thaw resistance and ductility [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on their ability to absorb water, paving blocks are divided into two categories, namely low permeable paving blocks and high permeable paving blocks. Paving blocks can be categorized as high permeable if they have an infiltration rate of more than 3 mm/s [5].…”
Section: Figure 1 Unused Construction Demolition Wastementioning
confidence: 99%
“…Higher w/cm ratio results in an increased workability of the cement paste, which can also be obtained at low w/cm ratios by using superplasticizers [7].…”
Section: Water To Cementitious Materials Ratio (W/cm)mentioning
confidence: 99%
“…Voids present in pervious concrete systems have been found to absorb sound quite efficiently [55]. Ng et al [7] recommend the void content of pervious concrete ranging from 15 % to 25 % as the acceptance criterion for ensuring the quality of concrete. Figure 5 shows the range of porosities adopted by previous researchers.…”
Section: Figure 5 Porosity or Void Ratio Range Adopted In Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation